Robert Baker account book - Baker, Robert, merchant and executor
Account book kept by Baker, a Jamaica resident, while serving as executor for several estates. Entries show a variety of expenditures, including the hiring out of slaves. There are additional account entries and household inventories which include slaves.
Merchant and executor from Jamaica.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Account books -- Jamaica; Slaves -- Jamaica; Slavery -- Jamaica; Executors; Merchants